Kartun biologi genetika Larry Gonick, Mark Wheels ; penerjemah, Tri Pujanarto ; penyunting, Christina M. Udiani - GONICK, Larry; Wheels, Mark; Tri Pujanarto; Udiani, Christina M (2001)
216 hlm ilus 21 cm